PRODUCT PLACEMENT OF KOPIKO CANDY IN THE KOREAN DRAMA "VINCENZO" ON THE INTEREST OF BUYING INDONESIAN CONSUMERS - Widiyanti, Dhea (The Commercium, 2022)
This study purposes to examine and analyze the significant effect of Kopiko candy product placement on consumer buying interest in K-Drama Vicenzo. This study uses a sample of 112 people who are members of the Vicenzo twitter group. The analysis technique used is multiple linear regression analysis. The results showed that all respondents' answers describing visual (X1), auditory (X2) and plot connection (X3) and buying interest (Y) kopiko candy on K-Drama Vicenzo showed a spread of answers in agree and strongly agree. Partially, product placement variables consisting of visual (X1), auditory (X2) and plot connection (X3) variables did not affect consumers' buying interest in Kopiko candy, only the auditory variable (X2) had a partial effect. However, simultaneously visual (X1), auditory (X2), and plot connection (X3) variables affect consumer buying interest in Kopiko candy products in K-Drama Vicenzo. Keywords: Buying Interest, Product Placement